New enchytraeid species from Mount Hallasan (Jeju Island, Korea) (Enchytraeidae, Oligochaeta) - Dózsa-Farkas, Klára; Felföldi, Tamás; Nagy, Hajnalka; Hong, Yong (Zootaxa, 2018)
The enchytraeid fauna of Mt. Hallasan (Jeju Island, Korea) was studied in 2016, and 21 enchytraeid species were recorded and identified in total. A combination of morphological and molecular analyses (based on CO1, ITS and H3 sequences) was applied. Here we give descriptions of eight new species of Enchytraeidae (Clitellata): Achaeta koreana sp. n., Achaeta macroampullacea sp. n., Bryodrilus hallasanensis sp. n., Chamaedrilus baekrokdamensis sp. n., Enchytronia seongpanakiensis sp. n., Mesenchytraeus jungsaihoi sp. n., Xetadrilus jejuensis sp. n. and Xetadrilus aphanoides sp. n. Additionally, two species were found to be new for the Korean fauna in Mt. Hallasan: Fridericia cf. paroniana Issel, 1904 and F. perrieri (Vejdovský, 1878); three potentially new Fridericia species require further studies. Furthermore, two terrestrial polychaetes, Hrabeiella periglandulata Pižl & Chalupský, 1984 and Parergodrilus heideri Resisinger, 1925, were recorded. For 12 enchytraeid species, DNA sequences are presented for the first time: these include, apart from the new species, further taxa such as species of Xetadrilus, a genus of which no sequences were previously available.